Sistem Pendeteksi Kebocoran Gas Lpg Menggunakan Sensor Gas Mq – 02 - Muhtajuddin Danny; Aditya Eka Sukma (Jurnal SIGMA, 2018)
LPG gas conversion is one of the government programs which became the modern household items at this time. Although LPG stove is have advantage simple to use than petroleum stove, but still have disadvantage dangerous if there are gas leak. As theri danger, so need a detector gas leak warning signal if there are leak. To get system that can be automatic operation, so need Arduino-uno as controller and using MQ-2 gas sensor. This device works when the MQ-2 gas sensor detects LPG gas on the normal condition of the air. System will use LPG gas sensor that usable to detect gas leak on gas stove equipment and this device has been made successfully and able to help as leakage detector of the LPG gas tube on the kitchen. The process of testing this system gets a sound notification and LED (Light Emitting Diode) that there has been a leak of LPG cylinders